A kitchen experiment for replicating lava-ice interaction on stratovolcanoes - Conway, Chris E.; Tani, Kenichiro; Sano, Takashi; Matsumoto, Keiko; Ishizuka, Osamu (Frontiers in Earth Science, 2023)
Many Quaternary stratovolcanoes host (or hosted) glacial ice with volumes that have fluctuated in response to long-term global climate cycles. The repeated advance and retreat of ice in valleys on the flanks of volcanoes throughout their eruptive histories has impacted how and where lava flows are preserved. Understanding the dynamics of lava-ice interaction is a vital part of reconstructing the growth histories of many stratovolcanoes and can provide valuable clues about the evolution of Earth’s climate. We have constructed a basic experiment, using common kitchen ingredients and utensils, to replicate the interaction between lava flows and glaciers on stratovolcanoes. This article outlines the ingredients and recipes for soda bread (stratovolcano analogue), ice cream (glacier analogues), and sauce (lava flow analogues), and describes exercises that provide qualitative lessons about the morphology of volcanoes, natural hazards, and paleoclimate.